The Difference in Effectiveness of 70% and 0.5% Chlorine to ReduceThe Germ Number on Stethoscope’s Membrane Experimental research at stethoscope in Baitul Izah Ward of Sultan Agung Islamic Hospital Semarang - Pramita, Heny; Saugi Abduh, Saugi Abduh; Chodidjah, Chodidjah (Sains Medika : Jurnal Kedokteran dan Kesehatan, 2011)
Background: Recently, nosocomial infection (hospital- acquired infections) is estimated to affects more than 1.4 million of in patients in all over the world. Stethoscope is one source of nosocomial infection caused by the continuous contact from one patient to another. 70% alcohol and 0.5% chlorine can be used for disinfection. The purpose of the research is to find out the difference in the effectiveness of 70% alcohol and 0.5% chlorine to reduce the amount of germ on the stethoscope’s membrane.Design and Methods: This was an experimental research with the Post Test Only Control Group Design using 18 stethoscopes divided into 3 groups randomly. Group A was the control group (aquabidest), group B were treated with 70% alcohol treatment, and group C was treated with 0.5% chlorine. The research samples were the stethoscopes used to treat patient in Baitul Izah ward of Islamic Hospital of Sultan Agung Semarang. The data on the germ amount was analyzed using Kruskal-Wallis test. Results: There was a significant difference between aquabidest group and 70% alcohol group (p<0.05) and between aquabidest control group and chlorine group(p>0.05), nevertheless, there was no significant difference between the 70% alcohol group and 0.5% chlorine group ( 0.652). Conclusion: There was no difference in the effectiveness between 70% alcohol and 0.5% chlorine to reduce the number of germ on the stethoscope’s membrane (Sains Medika, 3(1):63-68).